Wednesday

April 16, 2014

April 16, 2014

Posted by **Blossom** on Saturday, March 24, 2012 at 3:03pm.

- Trig -
**G**, Saturday, March 24, 2012 at 3:21pm(cosx/sinx X sinx)(1/cosx - cosx) = sin^2x

(cosx)(1-cos^2x) /cosx = sin^2x

1-cos^2x = sin^2x

sin^2x = sin^2x

PROVED

**Related Questions**

drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...

trig - express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Simplifying with Trigonometry Identities - Hi, I am a senior in High School ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Trigonometry - Prove the following trigonometric identities. please give a ...

Math - Im really struggling with these proving identities problems can somebody ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

trig - How do I prove these trig identities? secx-cosx/tanx =sinx And 1+sinx/...